Attitudes and knowledge of general practitioners in Northern Johannesburg, Gauteng, towards autism spectrum disorders in children - Patel, Reshma (My University, 2018)
CONTEXT: Lack of knowledge on Autism Spectrum Disorder (ASD) in general practitioners (GPs) has an impact on early diagnosis and therefore on early intervention. AIM OF STUDY: The aim of this study was to determine the knowledge and attitudes of GPs regarding ASD in children in Northern Johannesburg, Gauteng. DESIGN, SETTING AND PARTICIPANTS: A quantitative descriptive study design was applied using a cross sectional survey. GPs from Northern Johannesburg, were recruited at workshops or approached directly. METHODS: 52 GPs completed a questionnaire that assessed their knowledge and attitudes of ASD in children. RESULTS: Significant findings included 78% of respondents did not have a high level of accuracy in diagnosing ASD; 63.5% of respondents had never diagnosed a child with ASD; 52,3% of participants incorrectly believed that a delay in walking at 18 months of age was a red flag for ASD and 76% of participants correctly agreed that ASD holds a social stigma in their community. CONCLUSION: In this study the majority of GPs had not diagnosed a child with ASD and reported not having a high level of accuracy in diagnosing ASD. However, they were generally accurate with knowing the important symptoms necessary for the diagnosis of ASD. The majority of participants also believed that there is a negative attitude towards children diagnosed with ASD